A two‐step reaction scheme leading to singlet carbene species that can be detected under matrix conditions for the reaction of Zr(3F) with either CH3F or CH3CN. Issue 11 (24th February 2014) - Torres, Ana E.; Castro, Guadalupe; Pablo‐Pedro, Ricardo; Colmenares, Fernando
<x xml:space="preserve">Abstract</x> The results obtained from CASSCF‐MRMP2 calculations are used to rationalize the singlet complexes detected under matrix‐isolation conditions for the reactions of laser‐ablated Zr(3F) atoms with the CH3F and CH3CN molecules, without invoking intersystem crossings between electronic states with different multiplicities. The reaction Zr(3F) + CH3F evolves to the radical products ZrF· + ·CH3. This radical asymptote is degenerate to that emerging from the singlet channel of the reactants Zr(1D) + CH3F because they both exhibit the same electronic configuration in the metal fragment. Hence, the caged radicals obtained under cryogenic‐matrix conditions can recombine through triplet and singlet paths. The recombination of the radical species along the low‐multiplicity channel produces the inserted structures H3CZrF and H2CZrHF experimentally detected. For the Zr(3F) + CH3CN reaction, a similar two‐step reaction scheme involving the radical fragments ZrNC· + ·CH3 explains the presence of the singlet complexes H3CZrNC and H2CZr(H)NC revealed in the IR‐matrix spectra upon UV irradiation. © 2014 Wiley Periodicals, Inc.